Potential of KANGKONG (Ipomoea aquatica) as a PHYTOREMEDIATING AGENT on PHOSPHATE and NITRATE contaminated water. - Baldevarona, Ruby Rosa S. (UPHSI, 2009)
The study aimed to determine whether kangkong (Ipomoea aquatica) plant has a potential as a phytoremediating agent on phosphate and nitrate contaminated water. There were two treatments and two controls: a) phosphate-contaminated water with kangkong; b) phosphate-contaminated without kangkong; c) nitrate-contaminated water with kangkong; d) nitrate-contaminated water without kangkong. Each treatment and control had five replicates. The preparation, observation, and analysis were done at the University of the Philippines Visayas, College of Fisheries and Ocean Sciences, Institute of Aquaculture - Research Laboratory. Kangkong was acclimitized in distilled water for two days, after which they were distributed to the set-ups randomly with the phosphate, 0.01 mg per liter, and nitrate, 0.3 mg per liter, concentrations. Initial analysis was done. After five days, the final analysis was conducted. The initial and final phosphate and nitrate concentration in water were statistically analyzed using paired t-test. Percentage change in phosphate and nitrate concentrations treated with and without kangkiong was analyzed using Mann-Whitney U Test. Results showed that phosphate content of water with kangkong increased by 850.87% while that without kangkong had increased by 40.57% after five days. The nitrate in nitrate-contaminated water with kangkong decreased by 89.28% while that without kangkong had decreased by 6.83%. Pairec t-test showed that there was a significant increase in phosphate in phsosphate-contaminated water treated with kangkong and without kangkong. Also, there was a significant decrease in nitrate in nitrate-contaminated water treated with kangkong but not for nitrate in nitrate-cotaminated water not treated with kangkong. Mann-Whitney test showed that there was a significantly higher increase in phosphate in phosphate-contaminated water treated with kangkong than that without kangkong and significantly higher decrease in nitrate in nitrate-contaminated water treated with kangkong than that without kangkong. It is concluded that the addition of kangkong in eutrophic water increases phosphate and decreases the nitrate concentration within five days.